PENGARUH PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENANGGULANGAN KEMISKINAN DI KECAMATAN WOYLA KABUPATEN ACEH BARAT - Marwida, Nani; Mahrizal, Mahrizal (Ekonomika Journal, 2021)
Destitution is a fundamental problem faced by all countries, particularly developing countries like Indonesia. Destitution is a complex problem, so special attention is needed to overcome it. One of the poverty reduction efforts undertaken by the Government of Indonesia is through the Family Hope Program (PKH), which began to emerge in 2007.This research aim to find out and analyze the effect of the Family Hope Program on poverty alleviation in Woyla District, which is one of the areas that received assistance from the Family Hope Program. In this study using quantitative descriptive research methods. The object of this research is the Family Hope Program KPM in Woyla District. The data used are sourced from primary data in the form of answers to questionnaires, observations and secondary data from the government’s official website and the secretariat archives of Woyla District. Methods of data analysis carried out in the form of normality test and simple linear regression. The results of the analysis with the help of the SPSS 20 program indicate that there is a strong relationship between the variables of the Family Hope Program (PKH) and the poverty alleviation variable with a correlation coefficient of 0.601 and a determinant coefficient of 0.361. This means that the Family Hope Program (PKH) has a positive and significant effect on destitution reduction in Woyla District, this means that if the Family Hope Program increases, poverty reduction will also increase.